Pengembangan Modul Mata Kuliah Berbicara Berbasis Metode Jigsaw - Maulidia Tifani Alfin Nur Hardiana; Siti Aisah (IKIP PGRI Bojonegoro, 2021)
Abstract: This study aims to describe the initial trials of the speaking practice module using the jigsaw method for the Speaking and Learning course. This is a type of research and development (R&D) using the Borg & Gall development model which consist of several steps (1) analysis of need; (2) planning; (3) development of product; (4) validation and revision of product; and (5) trial of product. The trial of product was conducted on 12 students. The data was collected by using a product trials questionnaire to get student responses after using the speaking practice module that had been developed. The following are the results of research: (1) the availability of a speaking practice module that has been developed is able to facilitate and motivate students to practice speaking. (2) The product of the development of this speaking practice module consists of public speaking material, this jigsaw method is very helpful for students in understanding a type of speaking and explaining it to their friends in their group. (3) This product has met the product eligibility criteria shown from the results of the student response questionnaire with details on the presentation aspect with the